IMPLEMENTASI PENDIDIKAN AKHLAK UNTUK MEMBENTUK KARAKTER SISWA DALAM PERSPEKTIF PEMIKIRAN IBNU SINA - kulsum, ummu (Universitas Islam Madura, 2019)
Ibn Sina from his writings on the science of wisdom including the Book of an-Najah (Salvation) and the Book of al-Isyara wa'l-Tanbihat. Both of these books discuss moral education which can shape the character of students. Ibn Sina views humans as parables as the soul of plants, the soul of animals and the soul of humanity, the formulation of the problem is What is meant by moral education according to Ibn Sina? What is the implementation of moral education that can be used to shape student character? Moral education is meant by humans can get to know morals through themselves and through other people, both of which aim to find out the shortcomings of self so as to perfect themselves better than before. while implementation through moral guidance by way of habituation (adat) and thought. The purpose of the implementation of moral guidance is to gain knowledge and happiness, knowledge can only be achieved through a clean soul al-aql al-fa'al because with a clean soul will radiate knowledge to the soul, in these circumstances humans get true happiness.